Studying biodiversity of spiders species in seven different localities of Charsadda District, Khyber Pakhtunkhwa, Pakistan - Nooreen,N. (2024)
Abstract The current research work aims to provide knowledge about the diversity of spiders’ fauna and their occurrence throughout the year from District Charsadda Khyber Pakhtunkhwa, Pakistan. Research data were collected from March-2015 to January-2017 from seven different localities of Charsadda District by using the camera, bottle, plastic bags, paraffin films, field book and 70% of ethylene alcohol and 20% of glycerine were used as chemicals. By using special identification keys, spiders were differentiated into families, genera and species. During the study time, a total of 2734 specimens of spiders were collected belonging from 35 genera, 15 families and 44 species were identified. Salticidae was the dominant family according to genera studied plus spiders samples numbers collected with 10 genera and 616 species specimens count. The high occurrence of spiders was studied during July. The result of the current study also shows a reduction of spider’s species in December due to lowering the temperature. The current study shows that Salticidae were the dominant family as capered to other species. The occurrence of spiders species greatly depends on changing the weather condition. The present study also shows great fluctuation in spider’s occurrence with changing of hot climate to colder during the study duration. Moreover, the wet season plays a great role in spiders’ population increase and growth.